Peran Adat Manyonggot Dalam Mengatasi Trauma Masyarakat Melayu Tanjungbalai dan Keterkaitannya dengan Bimbingan Konseling Islami - Sari, Indah; Ritonga, Hasnun Jauhari (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
Manyonggot is a ceremonial tradition of picking up the spirit in the human soul which is carried out identically in a state of grief and regarding the sadness and distress experienced by someone. This Manyonggot activity is carried out by chanting words of encouragement and advice to people who are sick or have problems so that the problems faced can be resolved. This study aims to examine the role of the Manyonggot custom for individuals who have problems. The method in this research is qualitative phenomenology in which this research is conducted to find out the phenomena that occur in society and in accordance with the research topic. Then the data collection techniques in this study are observation, interviews, documentation and literature study. The results found in the study that this Manyonggot custom has a relationship with Islamic counseling guidance because this custom plays a role in restoring enthusiasm and providing advice and guidance to individuals who have problems, then in the process of overcoming the problem there are values of Islamic teachings in the process. The conclusion is that Manyonggot has a role in healing community trauma and has a relationship with the value of Islamic counseling where Manyonggot is an activity in providing direction in the form of good advice to individuals.